A review of programming code assessment approaches - Ul Qayyum, Noor; Abu Seman, Muhamad Sadry; Shah, Asadullah; Qureshi, Muhammad Shuaib; Raza, Ali (2019)
Learning computer programming language in harmony with practical coding actively while ensuring proper content progression is critical in introductory programming cources. Novice programmers usually face difficulty in acquiring the foundation level programming concepts adequately that usually lead to disappointmenet and ultimately back off. Bloom's Taxonomy has been generally adopted by the educators as a standard for assessing learning progression of students. In past there have been lot of research work on adopting Bloom's Taxonomy and its variants for computer programming languages, however, none has specially looked at an automatic mechanism to evaluate the six levels of Bloom's taxonomy on code level directly. In this paper we reviewed different approaches for assessment of programming code and discuss the challenges involved to implement the Bloom's taxonomy in programming languages directly on code level.